Pemanfaatan Media Online Mata Peristiwa sebagai Sarana Publikasi Narasi Berita oleh Humas Polres Sukabumi Kota - Jihan Syalina Wardah; Abung Supama Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to examine the strategic approach employed by the PublicRelations Division of Polres Sukabumi Kota in leveraging the online media platformMata Peristiwa for publication purposes, as well as to identify challengesencountered in this process. Utilizing a qualitative descriptive methodology, thefindings indicate that the publication strategy adheres to a structured internalworkflow. In this process, news drafts are initially handled by the Public InformationSection (Penmas) and subsequently verified by the Multimedia Information andDocumentation Section (PIDM) before being forwarded to the editorial team. Onaverage, the division disseminates 40 news narratives monthly. The identifiedchallenges include delays in acquiring statements from sources, limited humanresources, and the necessity for linguistic adjustments between formal institutionallanguage and online media. The study concludes that the deployment of specializedonline portals significantly enhances transparency and expedites the disseminationof police activity narratives to the public.